Kinematic and dynamic patterns of human gait reference data for young women walking at low, preferred and high speeds - Amadeusz Bartoszek; Sławomir Winiarski; Bogdan Pietraszewski (Kazimierz Wielki University, 2018)
The purpose of this study was to presents reference data concerning gait speed for angular, kinematic and dynamic temporal and spatial parameters in patterns of groud reaction forces, knee joint moments of force and powers during a wide range of walking speeds of young womens. For the purpose of the study, comprehensive measurements and descriptive statistics were used to describe dynamic and kinematic variables at each walking speed tested. The tree walking velocities levels (low, preferred and high) were selected as the research objectives. The results showed that along with the increase in walking speed, the values of the analysed parameters also increase.